2017
DOI: 10.1007/s00221-017-4936-1
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring the navigational field: individual predisposition towards field independence predicts preferred navigational strategy

Abstract: To successfully navigate within an environment, individuals have to organize the spatial information in terms of salient landmarks, paths and general layout of the navigational environment. They may differ in the strategy they adopt to orientate themselves, with some individuals preferring to use salient landmarks (landmark spatial style, L-SS), others preferring to plan routes or paths through an egocentric strategy in which landmarks are connected with each other (route spatial style, R-SS) and others still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 32 publications
5
20
0
1
Order By: Relevance
“…This interpretation is supported by a previous study showing that FI individuals are more likely to prefer and adopt a survey strategy, while FD ones are very likely to prefer and adopt a landmark strategy (Boccia et al, 2017a). These results allow to hypothesize that the evolved navigational strategy, namely the survey strategy, may be easily accessible to individuals with a FI CS, but not to those with a FD CS.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…This interpretation is supported by a previous study showing that FI individuals are more likely to prefer and adopt a survey strategy, while FD ones are very likely to prefer and adopt a landmark strategy (Boccia et al, 2017a). These results allow to hypothesize that the evolved navigational strategy, namely the survey strategy, may be easily accessible to individuals with a FI CS, but not to those with a FD CS.…”
Section: Discussionsupporting
confidence: 74%
“…Some results support this hypothesis. Indeed, Boccia et al (2017a) found FI individuals were more proficient in performing the “survey” tasks, that is tasks requiring participants to use an abstract, internal, object-based representation of the space, which almost corresponds to a “bird's-eye viewpoint” (i.e., survey representation) (Nori and Giusberti, 2006) and in present study FI were significantly better in both the map drawing tasks. The ability to represent in a map what has been acquired while exploring a novel environment depends on the ability to develop a cognitive map, that is an allocentric, survey representation of the environment (Iaria et al, 2007).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In a previous study on young adults, we analyzed the effects of field dependence–independence on different navigational tasks, finding that it did not affect performances on easier tasks such as route learning and landmark recognition but significantly affected those on more difficult tasks, such as those requiring to form a map‐like representation of the environmental space. In the latter, individuals were requested to restructure the egocentric information about the environment they acquired by active exploration in an abstract, allocentric representation (Boccia, Piccardi, et al., ; Boccia, Vecchione, et al., ). Instead, during route learning, individuals were requested to retrieve the path information as they have been processed (i.e., egocentrically).…”
Section: Discussionmentioning
confidence: 99%